Capital structure mediates the relationship of institutional ownership, asset structure, and company growth to the value of manufacturing companies - Tani, Lukas Gredyansyah; Winarno, Agung; Siswanto, Ely (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The stock price describes the rise and fall of a company's value. Manufacturing companies support economic growth and provide jobs in the uncertainty of the world economy. The company's continued optimal value will attract investors. The use of analysis wi th quantitative approaches and explanatory methods. Manufacturing companies listed on the Indonesia Stock Exchange are made objects of population. This study aims to ascertain the function of capital structure as a mediating variable and the relationship between institutional ownership, assetstructure, company growth, and company value. Quantitative research method using path analysis and Sobel test methods. Research tool using Eviews12 Purposive sampling was used to determine the sample using several criteria.71 manufacturing companies that met the requirements with observations for 4 years obtained a sample of 284. The results showed that company growth, asset structure, and institutional ownership did not affect company value, but capital structure significantly affected company value. Capital structure is strongly influenced by institutional ownership and company growth. However, it is not affected by the structure of the asset. Capital structure can mediate institutional ownership and a company's growth against company value. However, it cannot mediate the asset structure against the company's value.